Epigenetics of scleroderma: Integrating genetic, ethnic, age, and environmental effects. Issue 3 (October 2019) - Ramos, Paula S
Scleroderma or systemic sclerosis is thought to result from the interplay between environmental or non-genetic factors in a genetically susceptible individual. Epigenetic modifications are influenced by genetic variation and environmental exposures, and change with chronological age and between populations. Despite progress in identifying genetic, epigenetic, and environmental risk factors, the underlying mechanism of systemic sclerosis remains unclear. Since epigenetics provides the regulatory mechanism linking genetic and non-genetic factors to gene expression, understanding the role of epigenetic regulation in systemic sclerosis will elucidate how these factors interact to cause systemic sclerosis. Among the cell types under tight epigenetic control and susceptible to epigenetic dysregulation, immune cells are critically involved in early pathogenic events in the progression of fibrosis and systemic sclerosis. This review starts by summarizing the changes in DNA methylation, histone modification, and non-coding RNAs associated with systemic sclerosis. It then discusses the role of genetic, ethnic, age, and environmental effects on epigenetic regulation, with a focus on immune system dysregulation. Given the potential of epigenome editing technologies for cell reprogramming and as a therapeutic approach for durable gene regulation, this review concludes with a prospect on epigenetic editing. Although epigenomics in systemic sclerosis is in its infancy, future studies will help elucidate the regulatory mechanisms underpinning systemic sclerosis and inform the design of targeted epigenetic therapies to control its dysregulation.